Analisis Bimbingan Karir Teori Holland dalam Perencanaan Karir Siswa - Ramadhani, Erfan; Jannah, Ana Tul (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
The problem of this research is based on the fact that there are still many students who enter advanced schools at the will of their parents, students feel that they are wrong to enter the department because they do not match their talents, interests and potential.Furthermore, there have been efforts that have been made by guidance and counseling teachers in providing Holland theory career guidance services. The research method used is descriptive qualitative. The informants in this study were the Counseling Guidance Teacher and students. Data analysis in this study used data reduction steps, data presentation, and verification. The results of this study indicate that the implementation of Holland theory career guidance services has been running well. From the results of interviews, observations and documentation to research informants regarding the implementation of Holland theory career guidance services, it can be understood that at the planning, implementation, evaluation and follow-up stages it has gone well as it should, this is evident in the presence of service program plans, materials and instruments. Holland, as well as the results of the Holland instrument analysis of students who already know the personality type and direction of their career choices.